PENGARUH ELECTRONIC WORD OF MOUTH, HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PENGGUNAAN JASA OJEK ONLINE MAXIM - Adinda Faizatun Ni'am (2022)
Maxim is a type of public transportation that is an option for some individuals to support their daily mobility activities. For some, they think that using Maxim can be the right solution to deal with the hustle and bustle of traffic jams, especially in the capital city of Jakarta. Currently there are several phenomena that influence the decision to use Maxim's online motorcycle taxi so that the formulation of the problem is obtained related to whether Electronic Word of Mouth, price and service quality influence purchasing decisions. The target population in this study were active students of the Faculty of Economics and Business at UPN Veterans Jakarta, with a sample of 100 respondents using a non-probability sampling technique with a purposive sampling method. This research uses quantitative methods. The test equipment used is SPSS and Smart PLS 3.0. The results of this study indicate that the variables of Electronic Word of Mouth, price and service quality have an influence on the decision to purchase Maxim's online motorcycle taxi services for active management students at UPN Veteran Jakarta. Based on the statistical t test, the Electronic Word of Mouth variable shows a value of 0.760, the price variable shows a value of 0.221 and the service quality variable is 0.105. This means that Electronic Word of Mouth variables, price and service quality influence and increase consumer purchasing decisions.